Reading Without Spelling Book Improves Early Reading Ability in Preschoolers: Membaca Tanpa Buku Huruf Meningkatkan Kemampuan Membaca Dini pada Anak-Anak Pra-Sekolah - Nety Nur Kusuma Dewi; Luluk Iffatur Rocmah (Academia Open, 2025)
General Background: Early childhood is a critical period for language and literacy development, during which appropriate stimulation supports future academic readiness. Specific Background: Beginning reading ability in children aged 4–5 years involves recognizing letters, syllables, simple words, and simple sentences, yet many learners encounter difficulties when instruction relies heavily on spelling-based methods. Knowledge Gap: Although the Belajar Membaca Tanpa Mengeja (Reading Without Spelling) approach is widely used, empirical evidence regarding its classroom application through a structured learning book remains limited. Aims: This study aimed to examine the effect of implementing a Reading Without Spelling learning book on the early reading ability of children aged 4–5 years at TK Dharma Wanita Persatuan Tawangsari 2. Results: Using a quantitative quasi-experimental nonequivalent control group design with 30 participants, the experimental group achieved a higher mean posttest score (87.00) than the control group (78.11), with t(28) = 2.134 exceeding the critical value of 2.048 at α = 0.05, indicating a significant difference between groups. Novelty: The study evaluates a locally developed literacy book that introduces words holistically without letter-by-letter spelling, supported by visual illustrations and structured progression. Implications: The findings suggest that the Reading Without Spelling book can serve as a practical alternative learning medium for improving early reading ability and enriching literacy instruction in early childhood education settings. Highlights: Experimental participants achieved substantially higher post-assessment scores than peers receiving conventional instruction. Statistical testing confirmed a meaningful difference between the two instructional approaches at the 5% level. Holistic word recognition supported by visual cues corresponded with stronger literacy outcomes. Keywords: Early Reading Ability; Preschool Literacy; Reading Without Spelling; Quasi-Experimental Study; Early Childhood Education